Advances in the application of the Principal Static Wind Loads: A large-span roof case. (1st July 2022) - Frontini, Giorgio; Argentini, Tommaso; Rosa, Lorenzo; Rocchi, Daniele
Abstract: In this paper, a procedure to define a small set Multi-target Equivalent Static Wind Loads (M-ESWLs) that allows for the verification of a large set of structural elements of a stadium roof is presented and applied to a real case. The methodology, based on the combination of the so-called Principal Static Wind Loads (PSWLs), is aimed at reducing the subjectivity of the designer in the identification of the most challenging structural conditions induced by wind actions, and therefore it allows to simplify and speed up the wind-resistant design process of roof structures. Starting from wind tunnel tests on a scaled rigid model of a stadium, the dynamic response of its roof is computed by loading the finite element model of the structure with the time histories of the spatially averaged net pressures acting on its surface. The time histories of the internal forces acting in a set of structural members are reconstructed, and the target envelope is built by identifying, for each of them, a maximum and a minimum value through a statistical analysis of the time series. For each of these extreme conditions an ESWL is identified, PSWLs are computed and combined by means of a genetic algorithm, and the set of M-ESWLs, able to match the envelope, is defined. To limit the number of M-ESWLs, a nonlinear constrained optimization is implemented in the PSWLs combination, also introducing the possibility to over-dimension some structural members. It is concluded that the application of this methodology allows the designer to select a limited number of M-ESWLs that can be used in an automated way in order to verify the response of a defined set of structural elements. Graphical abstract: Highlights: A hybrid procedure for defining Multi-target Equivalent Static Wind Loads (M-ESWLs) is presented. A small number of M-ESWLs allows for the simulation of the wind induced stress in all the structural members. The M-ESWLs are obtained with a combination of the so-called Principal Static Wind Loads (PSWL), applying a genetic algorithm optimization. A large roof structure is used as test case, and results are compared against more common ESWL approaches. The M-ESWLs determined following the procedure are effective and can be easily combined with other design loads.